#TITLE_ALTERNATIVE# - RIZKYTUA HALOMOAN (NIM: 12909013); pembimbing: Ivonne M. Radjawane Ph. D ; Irsan Soemantri B, SAMUEL
The objective of this study is to measure sea temperature using underwater acoustic waves.Underwater acoustic waves can be used to measure the temperature profile of the sea because underwater acoustic wave propagation is strongly influenced by physical oceanographic parameters, especially temperature.Data used in this study are obtained from research and development activities namely International Nusantara Stratification and Transport (INSTANT) from Kementerian Kelautan dan Perikanan at Macassar Strait. The temperature, salinity and sound speed data (obtained from the above) are used as a comparison for the sound speed and the temperature model. Ray tracing method is used to trace the propagation of underwater acoustic waves, and then followed by the underwater acoustic tomography technique to calculate the underwater sound speed. Newton – Rhapson method also used to calculate the underwater temperature.The value of error model of the speed of sound obtained from this study is correlated with the condition number of the matrix. For a matrix with small condition number (valued at 1 in this study), the errors are small; 0,003% to 0,02% for the sound speed model and 0,12% to 0,63% for the temperature model. For a matrix with large condition number (valued at 1,225 x 1016) the errors are large, valued at 27% to 1067%. The condition number is used to determine how close a matrix to be singular (have an inverse or not), a matrix with large condition number doesn’t have an inverse, and a matrix with small condition number have an inverse. The large condition number matrix is identified in the isothermal seawater condition and the small condition number matrix is identified in the thermocline and deep layer. The example for a large condition number matrix is shown in appendix.